Novel melt-processable chitosan–polybutylene succinate fibre scaffolds for cartilage tissue engineering - Oliveira, J. T. (2011)
Novel chitosan/polybutylene succinate fibre-based scaffolds (C-PBS) were seeded with bovine articular chondrocytes in order to assess their suitability for cartilage tissue engineering. Chondrocytes were seeded onto C-PBS scaffolds using spinner flasks under dynamic conditions, and cultured under orbital rotation for a total of 6 weeks. Non-woven polyglycolic acid (PGA) felts were used as reference materials. Tissue-engineered constructs were characterized by scanning electron microscopy (SEM), hematoxylin-eosin (H&E), toluidine blue and alcian blue staining, immunolocalization of collagen types I and II, and dimethylmethylene blue (DMB) assay for glycosaminoglycans (GAG) quantification at different time points. SEM showed the chondrocytes' typical morphology, with colonization at the surface and within the pores of the C-PBS scaffolds. These observations were supported by routine histology. Toluidine blue and alcian blue stains, as well as immunohistochemistry for collagen types I and II, provided qualitative information on the composition of the engineered extracellular matrix. More pronounced staining was observed for collagen type II than collagen type I. Similar results were observed with constructs engineered on PGA scaffolds. These also exhibited higher amounts of matrix glycosaminoglycans and presented a central region which contained fewer cells and little matrix, a feature that was not detected with C-PBS constructs.